Institutional maintenance and elite sport: a case study of high-performance women`s ice hockey in Canada - Edwards, J.; Stevens, J. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
The purpose of this study was to examine how Canadian women`s hockey stakeholders view the elite female hockey program and its impact upon the ability of a player to progress along the athlete development pathway. This research applied institutional work through institutional maintenance to address this purpose. A total of 21 semi-structured interviews were conducted with players, parents, coaches and administrators with experience within elite female ice hockey programs. The finding indicated a static approach that mimicked the dominant male elite sport development model that both enabled and constrained the opportunities for female players to advance to high performance levels. The implications for the future success of women`s elite hockey in Canada, and the value of the Canadian model as an exemplar to countries building their female hockey systems are discussed.